Management and Prevention of Multidrug-Resistant Bacteria in War Casualties - Diana Isabela Costescu Strachinaru; Céline Ragot; Anke Stoefs; Nicolas Donat; Pierre-Michel François; Peter Vanbrabant; Alexia Verroken; Frédéric Janvier; Patrick Soentjens (Tropical Medicine and Infectious Disease)
The growing threat of antimicrobial resistance (AMR) is a critical issue for both civilians and the military. With each successive conflict, pathogens become more resistant, making the management of infections in casualties increasingly challenging. To better understand the scope and characteristics of conflict-related AMR, a comprehensive literature search was conducted in the PubMed database in April 2025, using defined search terms related to war casualties and antimicrobial resistance. We screened and included 117 relevant publications, comprising original research articles, reviews, case series, case reports, editorials, and commentaries, published in English or French, with no date restriction. This narrative review synthesizes current evidence on multidrug-resistant bacteria most commonly isolated from war casualties, their associated resistance mechanisms, and the microbiological diagnostic tools available at various levels of the military continuum of care (Roles 1–4). It also presents strategies for preventing cross-contamination and infection in resource-limited combat settings and provides practical, field-adapted recommendations for clinicians, from first responders to specialized care providers, aiming to improve infection management in armed conflict zones and mitigate the spread of AMR.